Acute Compartment Syndrome of the Thigh: A Case Report - Karakurt, Lokman; Köse, Rüştü (Fırat University, 2002)
Compartment syndrome of the thigh is a rare condition. In this study, we discussed a case with type IIIa open femoral fractures who had acute compartment syndrome of the thigh after the surgical treatment. 65 years-old man with bilateral open femoral fractures had wound debridement and 18 days after that, osteosentesis with kunther interlocking nail was performed. At the day 6th postoperatively, he had extremely tense left thigh, loss of dorsiflexion and dorsal anestesia on the left foot. Urgent surgery was performed by using old lateral skin incision and after the faciotomy all compartment were released and 2500 cc hematom was drained. A branch of a. profunda femoris which was the responsible for bleeding was tied. Clinical appearence due to compartment syndrome was improved completely after operation.

Uyluğun kompartman sendromu nadir görülen bir durumdur. Biz, sol femur diafiz tip IIIa açık kırığı olan bir hastada ameliyat sonrası geç dönemde meydana gelen uyluk akut kompartman sendromunu literatür bilgileri altında tartışmayı amaçladık. 65 yaşında ateşli silah yaralanmasına bağlı sol femur diafiz tip IIIa açık kırığı ve sağ femur subtrokanterik kırığı olan erkek hastaya ilk gün acil olarak yapılan yara debridmanını takiben 18. günde kilitli küntcher çivisi ile bilateral intrameduller osteosentez uygulandı. İkinci ameliyattan 6 gün sonra sol uylukta aşırı gerginlik, ayağa dorsal fleksiyon yaptıramama ve ayak dorsalinde duyu kaybı mevcuttu. Hasta acil ameliyata alınarak önceki lateral insizyondan fasyatomiyi takiben kompartmanlara ulaşıldı ve yaklaşık 2500 cc hematom boşaltıldı. Kanama nedeni olan a.profunda femorisin dalı bulunup bağlandı. Ameliyat sonrasında kompartman sendromuna bağlı olarak gelişen klinik tablo tamamen düzeldi.
UYLUĞUN AKUT KOMPARTMAN SENDROMU: OLGU SUNUMU